Intrinsic Motivation as a Mediator of the Effects of Work-Life Balance, Work Environment, and Work Discipline on Public Sector Employee Performance - Duta Mustajab; Abdul Rasyid; Novi Darmayanti (Advances in Human Resource Management Research, 2025)
Purpose: This study aims to analyze the influence of work-life balance, work environment, and work discipline on employee performance in public-sector organizations, and to examine the role of intrinsic motivation as a mediating variable in the relationships among these variables. Research Design and Methodology: This study employs a quantitative, associative design. Data was collected through a structured questionnaire distributed to employees at 40 Regional Government Agencies (OPDs) in Papua Province, with a total of 109 respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the direct and indirect effects between variables Findings and Discussion: The results of the study indicate that work-life balance, work discipline, and intrinsic motivation have a direct and significant effect on employee performance; the work environment has a significant effect on intrinsic motivation; and intrinsic motivation was found to partially mediate the relationship between the work environment and employee performance, but does not mediate the effects of work-life balance and work discipline on performance. These findings suggest that employee performance is more influenced by internal motivational processes that are shaped by the work environment. Implications: This study makes a theoretical and practical contribution by emphasizing the importance of intrinsic motivation as a psychological mechanism for improving employee performance. In practical terms, public sector organizations need to create a conducive work environment and strengthen strategies to enhance intrinsic motivation, thereby boosting employee performance, particularly in regions with unique characteristics, such as Papua Province.